Espécies do gênero Lucifer Thompson, 1829 no litoral brasileiro (Decapoda: Luciferidae) - D'Incao, Fernando (1997)
The species of the family Luciferidae in Brazil sere revised. They are represented by Lucifer faxoni that occurs in coastal waters including estuaries, and Lucifer typus an ofsshore specie.